Compressive strength and durability of foamed concrete incorporating processed spent bleaching earth - Rokiah, O.; Khairunisa, Muthusamy; Mohd Arif, S.; Youventharan, D.; Putra Jaya, Ramadhansyah; Chong, Beng Wei; Mohd Mustafa, Al Bakri Abdullah; Mangi, Sajjad Ali; Nabiałek, Marcin; Śliwa, Agata (Polish Academy of Sciences, 2022)
Foamed concrete incorporating processed spent bleaching earth (PSBE) produces environmentally friendly foamed concrete. Compressive strength, porosity, and rapid chloride penetration tests were performed to investigate the potential application for building material due to its low density and porous concrete. Laboratory results show that 30% PSBE as cement replacement in foamed concrete produced higher compressive strength. Meanwhile, the porosity of the specimen produced by 30% PSBE was 45% lower than control foamed concrete. The porosity of foamed concrete incorporating PSBE decreases due to the fineness of PSBE that reduces the volume of void space between cement and fine aggregate. It was effectively blocking the pore and enhances the durability. Consistently, the positive effect of incorporating of PSBE has decreased the rapid chloride ion permeability compared to that control foamed concrete. According to ASTM C1202-19 the foamed concrete containing 30% PSBE was considered low moderate permeability based on its charge coulombs value of less than 4000. Besides, the high chloride ion permeability in foamed concrete is because the current quickly passes through the specimen due to its larger air volume. In conclusion, incorporating PSBE in foamed concrete generates an excellent pozzolanic effect, producing more calcium silicate hydrate and denser foamed concrete, making it greater, fewer voids, and higher resistance to chloride penetration.